2022
DOI: 10.1080/02670836.2022.2079862
|View full text |Cite
|
Sign up to set email alerts
|

Carbides precipitation and kinetics of H13 steel subjected to deep cryogenic treatment

Abstract: The influence of deep cryogenic treatment (DCT) on carbides precipitation and isothermal softening behaviour as a function of both temperature and time during tempering of H13 steel was investigated. The results show that the retained austenite transformed into martensite leading to an increase in hardness. The carbon content of martensite decreased after DCT and tempering according to the calculation of the X-ray diffraction spectrum. This indicates that more fine carbides precipitated from the martensitic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Khajuria et al [ 21 ] have pointed out that the prior austenite grain boundaries (PAGB) and lath grain boundaries are decorated with fine M 23 C 6 in different morphologies and sizes during tempering of P91 steel. According to the obtained results of Li et al, [ 22 ] the type of the precipitated carbides has been determined as M 23 C 6 during tempering, and the type of precipitated carbide are not changed after deep cryogenic treatment. The white precipitates that decorate PAGB region were analyzed by EDS.…”
Section: Resultsmentioning
confidence: 99%
“…Khajuria et al [ 21 ] have pointed out that the prior austenite grain boundaries (PAGB) and lath grain boundaries are decorated with fine M 23 C 6 in different morphologies and sizes during tempering of P91 steel. According to the obtained results of Li et al, [ 22 ] the type of the precipitated carbides has been determined as M 23 C 6 during tempering, and the type of precipitated carbide are not changed after deep cryogenic treatment. The white precipitates that decorate PAGB region were analyzed by EDS.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Villa et al [152,176,177] reported almost no change in tetragonality for cryogenically treated 1% C-1.5% Cr steel. Other investigators [21,125,184,194] have proven experimentally the very low tetragonality of the martensitic lattice for cryogenically treated Vanadis 6, X220CrVMo13-4, DC 53, and AISI H13 steels, while Das et al [12,53] assumed and Pellizzari et al [195] experimentally proved increased lattice tetragonality in AISI D2 steel (note that these steels will be discussed in Section 3.4).…”
Section: Microstructural Changes Due To Cryogenic Treatmentmentioning
confidence: 97%
“…However, the outcomes manifested clear differences. For instance, Li et al [125] and Lopez-Leyva et al [257] reported a significant reduction (but not complete elimination) of retained austenite, while Amini et al [258] claimed complete elimination of this phase by cryogenic treatment at −196 • C. Figure 13 shows the differences between conventionally quenched, conventionally quenched and tempered, and cryogenically treated and tempered AISI H13 steel. It is seen that conventionally quenched and untempered steel contains well-visible primary austenite grains, whereas the microstructure is martensitic, shown in Figure 13a.…”
Section: Hot Work Tool Steelsmentioning
confidence: 99%
See 2 more Smart Citations